Novel patients with NHLRC2 variants expand the phenotypic spectrum of FINCA disease - Tallgren, Antti; Kager, Leo; O’Grady, Gina; Tuominen, Hannu; Körkkö, Jarmo; Kuismin, Outi; Feucht, Martha; Wilson, Callum; Behunova, Jana; England, Eleina; Kurki, Mitja I.; Palotie, Aarno; et al. (Frontiers in Neuroscience, 2023)
Purpose: FINCA disease (Fibrosis, Neurodegeneration and Cerebral Angiomatosis, OMIM 618278) is an infantile-onset neurodevelopmental and multiorgan disease. Since our initial report in 2018, additional patients have been described (Brodsky et al., 2020; Rapp et al., 2021; Badura-Stronka et al., 2022). FINCA is the first human disease caused by recessive variants in the highly conserved NHLRC2 gene. Our previous studies have shown that Nhlrc2-null mouse embryos die during gastrulation, indicating the essential role of the protein in embryonic development. Defect in NHLRC2 leads to cerebral neurodegeneration and severe pulmonary, hepatic and cardiac fibrosis. Despite having a structure suggestive of an enzymatic role and the clinical importance of NHLRC2 in multiple organs, the specific physiological role of the protein is unknown. Methods: The clinical histories of five novel FINCA patients diagnosed with whole exome sequencing were reviewed. Segregation analysis of the biallelic, potentially pathogenic NHLRC2 variants was performed using Sanger sequencing. Studies on neuropathology and NHLRC2 expression in different brain regions were performed on autopsy samples of three previously described deceased FINCA patients. Results: One patient was homozygous for the pathogenic variant c.442G>T, while the other four were compound heterozygous for this variant and two other pathogenic NHLRC2 gene variants. All five patients presented with multiorgan dysfunction with neurodevelopmental delay, recurrent infections and macrocytic anaemia key features. Interstitial lung disease was pronounced in infancy but often stabilised. Autopsy samples revealed widespread, albeit at a lower intensity than the control, NHLRC2 expression in the brain. Conclusions: This report expands on the characteristic clinical features of FINCA disease. Presentation is typically in infancy, and although patients can live to late adulthood, the key clinical and histopathological features are fibrosis, infection susceptibility/immunodeficiency/intellectual disability, neurodevelopmental disorder/neurodegeneration and chronic anaemia/cerebral angiomatosis (hence the acronym FINCA) that enable an early diagnosis confirmed by genetic investigations.